2017
DOI: 10.1016/j.scitotenv.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of yield gains under climate change due to genetic modification of pearl millet

Abstract: Developing cultivars with traits that can enhance and sustain productivity under climate change will be an important climate smart adaptation option. The modified CSM-CERES-Pearl millet model was used to assess yield gains by modifying plant traits determining crop maturity duration, potential yield and tolerance to drought and heat in pearl millet cultivars grown at six locations in arid (Hisar, Jodhpur, Bikaner) and semi-arid (Jaipur, Aurangabad and Bijapur) tropical India and two locations in semi-arid trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 36 publications
6
43
0
Order By: Relevance
“…Similar to findings from Traore et al (2017), relative yield losses were lower for millet than maize (and additionally sorghum in our case). Likewise, Adiku et al (2015) and Singh et al (2017) reported positive impacts of climate change on millet yields in the region when [CO 2 ] effects were included for some locations and climate models. Millet is generally considered the most heat and drought tolerant cereal crop (Varshney et al 2017) and this is reflected in the models (e.g.…”
Section: Implications Of 15 • C Versus 20 • C Warmingmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to findings from Traore et al (2017), relative yield losses were lower for millet than maize (and additionally sorghum in our case). Likewise, Adiku et al (2015) and Singh et al (2017) reported positive impacts of climate change on millet yields in the region when [CO 2 ] effects were included for some locations and climate models. Millet is generally considered the most heat and drought tolerant cereal crop (Varshney et al 2017) and this is reflected in the models (e.g.…”
Section: Implications Of 15 • C Versus 20 • C Warmingmentioning
confidence: 97%
“…If drought stress is in fact increasing, it implies that there may be little opportunity to adopt longer season varieties to gain back the portion of the season (and radiation capture) lost due to accelerated development. Results reported by Singh et al (2017) indicated that drought and heat tolerant cultivars with long duration will be needed under climate change to avoid yield losses. This is an aspect that should be evaluated in more detail and could be assessed by adding simulations with potential yield levels and quantifying the yield changes due to water stress in each warming scenario.…”
Section: Drivers Of Yield Changesmentioning
confidence: 99%
“…Hence, this deep-root system does not require a high quantity of fertilizer in comparison with other crops. Pearl millet (Pennisetum glaucum) accounts for more than 50% of the global millet production [64]. Compared to traditional cereal crops, pearl millet requires lower amounts of resources for its growth and can grow in adverse conditions (e.g., water and fertilizer shortage) due to its physiological characteristics [24,65].…”
Section: Milletmentioning
confidence: 99%
“…They recommend the expansion of millet plantations in the province due to the rising temperature [69]. Furthermore, a study simulated the impact of temperature change on the yield of millet through a modified CSM-CERES-Pearl millet simulation model [64]. The results found that the millet yield increased by 6% after drought (lower limit of soil water availability) and 8% after heat simulation (increased from 27 • C to 29 • C).…”
Section: Milletmentioning
confidence: 99%
“…It is also gluten-free and has hypoallergenic properties [4]. In a context of climate change leading to unpredictable weather patterns and rising temperatures in West Africa [5, 6], pearl millet could play an even more important role for food security because it can withstand hot and dry conditions that would lead to the failure of other locally grown cereal crops such as maize or sorghum. However, pearl millet lags far behind other cereals in terms of breeding and its yield is low.…”
Section: Introductionmentioning
confidence: 99%